THE ROLE OF CULTURAL DIPLOMACY AND “SOFT POWER” IN THE RELATIONS OF UZBEKISTAN WITH THE EUROPEAN UNION - Ismatullayev Farhodjon Odiljonovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article analyzes the role of cultural diplomacy in strengthening the cooperation of the Republic of Uzbekistan with the European Union. The author points out that these contacts are carried out especially within the framework of days of culture, appearances, festivities, conferences, film and theater weeks on the basis of scientific sources, davriy press and archival materials